Mellem underholdende kedsomhed og bedøvende overstimulering: Affektive rytmer i oplevelsen af hashtag-fænomenet #ProudBoys på Twitter - Friis, Joachim Aagaard (MedieKultur: Journal of media and communication research, 2022)
This article explores what role minor and ambivalent feelings play in the experi- ence of hashtag phenomena on social media. The case study is the hashtag-flooding phenomenon that happened on Twitter in the autumn of 2020, where a group of homosexual men and supporters started using the hashtag #ProudBoys to change its connotation to the eponymous far-right group. With an affect-driven autoethnographic analysis, I explore how minor feelings are engendered in the experience of the #ProudBoys-phenomenon and how they are part of the affective public that is created in the activity of producing a new context for the hashtag. I conclude with the proposition that minor feelings had a significant effect on how my attention was kept while engaging in the #ProudBoys-phenomenon on Twitter. Furthermore, I propose that the phenomenon is an example of hashtag activism that is characterized more by everyday collective identity-building than acute urgency around a public matter.